2019
DOI: 10.1080/15384101.2019.1667705
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderiol F purified from Ganoderma leucocontextum retards cell cycle progression by inhibiting CDK4/CDK6

Abstract: This study was designed to purify molecules possess anti-cancer cell activity from the fruit body of Ganoderma leucocontextum. Bio-activity-guided purification and chromatographic separation of Ganoderma leucocontextum extract led to the enrichment of bioactive fractions and isolation of a single compound. The purified compound was identified as Ganoderiol F, which induced cancer cell death. In the in vivo experiments, we founded ethanol extract and ethyl acetate fraction inhibited tumor growth in the mice inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Ganoderma leucocontextum is a new species of Ganoderma discovered in southwestern China in 2014 [16]. Several studies have revealed that terpenoids from G. leucocontextum possess potential beneficial effects, including antidiabetic [17], antitumor [18], and neuroprotective activities [19]. However, the structural characteristics and antioxidant activities of polysaccharides from G. leucocontextum remain mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma leucocontextum is a new species of Ganoderma discovered in southwestern China in 2014 [16]. Several studies have revealed that terpenoids from G. leucocontextum possess potential beneficial effects, including antidiabetic [17], antitumor [18], and neuroprotective activities [19]. However, the structural characteristics and antioxidant activities of polysaccharides from G. leucocontextum remain mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 is an essential regulator of the G1-S transition in response to growth factor stimulation in cells [22], CDK4 and CDK6 are also critical factors for G1-S transition. [23] We found that the relative mRNA expression of CDK6 and CYCLIN D1 dramatically decreased with the treatment of JQ1 (Fig. 2d and 2f).…”
Section: Jq1 Arrested Cell Cycle Of Mv-4-11 Cell Lines At G0/g1 Phasementioning
confidence: 76%
“…Studies have shown that the overexpression of CDKs could cause the tumor proliferation to go out of control and lead to tumor malignancy and metastasis [ 33 , 34 ]. Inhibiting or downregulating the expression of CDK2 and CDK4 delays or inhibits cell cycle progression and reduces tumor proliferation and metastasis [ 35 37 ]. This finding was also consistent with the results of the present research.…”
Section: Discussionmentioning
confidence: 99%